A metropolitan-scale, three-dimensional agent-based model to assess the effectiveness of the COVID-19 Omicron wave interventions in a hyperdense city: a case study of Hong Kong. (September 2022) - Koh, Keumseok; Tang, Ka Chung; Axhausen, Kay; Loo, Becky P.Y.
Highlights: A novel, 3D agent-based model simulated the COVID-19 Omicron spread in Hong Kong Stringent interventions would be most effective during the peak time of the Omicron wave Flexible long-term strategies may be needed for managing future infectious diseases Abstract: We simulated the COVID-19 Omicron spread in Hong Kong, China, by building a novel three-dimensional agent-based model that incorporates its vertically expanded, hyperdense urban environment. The model examined the effectiveness of the 'zero-COVID' interventions (i.e., Compulsory Universal Testing (CUT) and citywide lockdown) that were for debate during the Omicron wave in Hong Kong. We found that such stringent interventions would be effective only with even faster and stricter implementation. Therefore, flexible long-term strategies should also be considered to contain and prevent future infectious diseases.